THE USE OF “BIG CITY ADVENTURE SYDNEY AUSTRALIA SOFTWARE GAME” IN ENHANCING THE STUDENTS’ VOCABULARY: A Classroom Action Research - Herlina, Rika; Akib, Erwin; Ma'ruf, Amar (FKIP Unismuh Makassar, 2018)
This research aimed to find out the improvement of students’ vocabulary by using Big City Adventure Sydney Australia Software Game as learning method and to know the students’ attitude towards using media game in learning vocabulary at SMAN 13 Luwu. The researcher used Classroom Action Research as the research method. The researcher conducted two cycles; each cycle consisted of three meetings. It was done at class XI IPA2 which consist 36 students. The research findings indicated that Big City Adventure Sydney Australia Software Game improved the students’ English vocabulary that focus on noun. It was proved by the improvement of the students’ achievement. Before treatment, the students’ vocabulary was very poor. Only 3 students (8.33%) got Good score. Most of the students are difficult in memorizing some vocabularies. At the end of the first cycle, any 9 students (25%) got Good score. In the second cycle, any 19 students (52.77%) got Good score. the mistake made by students in stressing syllables decreased, and the words that they memorize had increased. Finally, the students’ result of the cumulative vocabulary test there are 2 students (5.55%) got excellent score and 25 students (69.44%) got Good score. It could be concluded that use of Big City Adventure Sydney Australia Software Game was improve significantly of the students’ achievement. The students’ attitude in memorizing English words, It was proves that the presence of Game as a method and media improved the students’ enthusiasm in learning and also enhanced the students’ participant during learning process